DAMPAK SOSIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA GENERASI Z - Nurhasanah Nurhasanah; Risnawati Risnawati; Maulana Dwi Sena; Nabila Saputri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the impact of social media marketing on purchasing decisions in Generation Z. The rapid development of social media makes digital platforms an important marketing tool in influencing consumer behavior. This study uses a quantitative approach with a survey method by distributing questionnaires to 50 Generation Z respondents who actively use social media. The data obtained were analyzed using SPSS (Statistical Package For the Social Sciences) version 27 For Windows program analysis techniques to determine the extent of the impact of social media marketing on purchasing decisions. The results of the study indicate that social media marketing has a significant influence on purchasing decisions in Generation Z. This indicates that marketing strategies through social media have an important role in encouraging interest and purchasing decisions of Generation Z. Keyword: Social Media Marketing, Purchase Decision. Abstrak: Penelitian ini bertujuan untuk menganalisis dampak social media marketing terhadap keputusan pembelian pada Generasi Z. Perkembangan media sosial yang pesat menjadikan platform digital sebagai sarana pemasaran yang penting dalam memengaruhi perilaku konsumen. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei melalui penyebaran kuesioner kepada 50 responden Generasi Z yang aktif menggunakan media sosial. Data yang diperoleh dianalisis menggunakan teknik analisis program SPSS (Statistic Package For the Social Sciens) versi 27 For Windows untuk dapat mengetahui seberapa besar dampak social media marketing terhadap keputusan pembelian. Hasil penelitian menunjukkan bahwa social media marketing berpengaruh signifikan terhadap keputusan pembelian pada Generasi Z. Hal ini menunjukkan bahwa strategi pemasaran melalui media sosial memiliki peran penting dalam mendorong minat dan keputusan pembelian Generasi Z. Kata kunci: Social Media Marketing, Keputusan Pembelian.